2016
DOI: 10.1111/1462-2920.13531
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and microbial community determinants of reductive dechlorination at a site biostimulated with glycerol

Abstract: Biostimulation is widely used to enhance reductive dechlorination of chlorinated ethenes in contaminated aquifers. However, the knowledge on corresponding biogeochemical responses is limited. In this study, glycerol was injected in an aquifer contaminated with cis-dichloroethene (cDCE), and geochemical and microbial shifts were followed for 265 days. Consistent with anoxic conditions and sulfate reduction after biostimulation, MiSeq 16S rRNA gene sequencing revealed temporarily increased relative abundance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 101 publications
2
41
0
1
Order By: Relevance
“…However, these efforts have arguably enhanced replicability rather than reproducibility, by providing widely adopted defaults 5 . To this end, Drummond 6 suggested that exact replication of an experiment (i.e., replicability) is less informative (although a necessary pre-requisite for any scientific endeavour) than the corroboration of findings by reproduction in different independent setups (i.e., reproducibility) 7 , because biological findings that are robust to independent methodologies are arguably more dependable than any single-track analysis 5 . This distinction is highly relevant for the field of microbial ecology, where replicability is often confused with reproducibility, which is apparent from many often non-interchangeable methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these efforts have arguably enhanced replicability rather than reproducibility, by providing widely adopted defaults 5 . To this end, Drummond 6 suggested that exact replication of an experiment (i.e., replicability) is less informative (although a necessary pre-requisite for any scientific endeavour) than the corroboration of findings by reproduction in different independent setups (i.e., reproducibility) 7 , because biological findings that are robust to independent methodologies are arguably more dependable than any single-track analysis 5 . This distinction is highly relevant for the field of microbial ecology, where replicability is often confused with reproducibility, which is apparent from many often non-interchangeable methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Although new clustering algorithms that reduce the influence of clustering parameters, such as a hard cutoff for cluster similarity, have been specifically developed for amplicons 17 , cluster generation is context-dependent, i.e. different datasets generate different clusters, and different algorithms may produce different endresults 5,18 . Therefore, even though the same analysis framework is used, independent studies remain incomparable at OTU level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations